CHEMICAL ENGINEERING AND CHEMICAL PROCESS TECHNOLOGY - Mishra, Nigam M., contributor 642624; Stolarzewicz, Izabela, contributor 642625; Cannaerts, David, contributor 642626; Schuermans, Joris, contributor 642627; Lavigne, Rob, contributor 642628; Looz, Yannick, contributor 642629; Landuyt, Bart, contributor 642630; Schoofs, Liliane, contributor 642631; Schols, Dominique, contributor 642632; Paeshuyse, Jan, contributor 642633; Hickenbotham, Peter, contributor 642634; Clokie, Martha, contributor 642635; et al. (United Kingdom : Koros Press Limited, 2021)
Chemical engineering is a branch of engineering that deals with the production and manufacture of chemical products by chemical processes. This involves the construction of machinery, systems and processes for refining raw materials and for mixing, compounding and processing chemicals for the manufacture of valuable goods. Chemical engineering is as old as the process industry. The history derives from the cycles of fermentation and evaporation of early civilizations. Modern chemical engineeringoriginatedwiththe growth of large-scale chemical manufacturing operations in the second half of the 19th century. Throughout its growth as an independent discipline, chemical engineering has been oriented towards solving problems in the design and operation of large plants for continuous production. The production of chemicals in the mid-19th century consisted of small handicraft operations. Increased demand, public concern over the emission of toxic effluents and rivalry between competing processeshave created opportunities for greater efficiency. This led to the creation of combinations of capital for larger operations and contributed to the transition from the design field to the science-based industry.